Review of the Comprehensive Public Health Dentistry Approach towards Total Oral Health (International Journal of Food and Nutritional Sciences, 2022)
The dental conscience of the country is public health dentistry (PHD). Since its establishment in 1969, PHD speciality in India has contributed to the improvement of oral health conditions; nonetheless, there hasn't been much said about reaching universal oral health. With the goal of obtaining total oral health, the current review study was conducted to comprehend and analyse the existing situation of PHD. The various comprehensive approaches in PHD can be implemented effectively, including: the promotion of oral health should be done in a more creative and effective manner with various areas, such as dental health advocacy and literacy campaigns, national integrated health navigation systems, school-based dental clinics and oral health education in school curricula, dental health emergency helpline and response system, etc.; Also, the public-private partnership for the various comprehensive approaches in PHD can be effectively implemented. As well as the expansion of the health care delivery system's ability to reach people at the grassroots level, reaching rural areas through regular rural dental health care programmes, and creating specialised dental health care wings for those who require particular treatment. Therefore, a full approach to oral health care will depend more on having a thorough understanding of the fundamentals and implementing all relevant comprehensive techniques, or PHD.